Glycosylation Steps during Spiramycin Biosynthesis in Streptomyces ambofaciens: Involvement of Three Glycosyltransferases and Their Interplay with Two Auxiliary Proteins - Nguyen, Hoang Chuong (American Society for Microbiology (ASM), 2010)
Streptomyces ambofaciens synthesizes spiramycin, a 16-membered macrolide antibiotic used in human medicine. The spiramycin molecule consists of a polyketide lactone ring (platenolide) synthesized by a type I polyketide synthase, to which three deoxyhexoses (mycaminose, forosamine, and mycarose) are attached successively in this order. These sugars are essential to the antibacterial activity of spiramycin. We previously identified four genes in the spiramycin biosynthetic gene cluster predicted to encode glycosyltransferases. We individually deleted each of these four genes and showed that three of them were required for spiramycin biosynthesis. The role of each of the three glycosyltransferases in spiramycin biosynthesis was determined by identifying the biosynthetic intermediates accumulated by the corresponding mutant strains. This led to the identification of the glycosyltransferase responsible for the attachment of each of the three sugars. Moreover, two genes encoding putative glycosyltransferase auxiliary proteins were also identified in the spiramycin biosynthetic gene cluster. When these two genes were deleted, one of them was found to be dispensable for spiramycin biosynthesis. However, analysis of the biosynthetic intermediates accumulated by mutant strains devoid of each of the auxiliary proteins (or of both of them), together with complementation experiments, revealed the interplay of glycosyltransferases with the auxiliary proteins. One of the auxiliary proteins interacted efficiently with the two glycosyltransferases transferring mycaminose and forosamine while the other auxiliary protein interacted only with the mycaminosyltransferase.